On the frame set of the second-order B-spline - ATINDEHOU, Abdou Ganiou Débayo; Frederick, Christina; Kouagou, Yebeni B.; Okoudjou, Kasso A. (My University, 2022)
The frame set of a function g ∈ L 2 (R) is the set of all parameters (a, b) ∈ R 2+ for which the collection of time-frequency shifts of g along aZ × bZ form a Gabor frame for L 2 (R). Finding the frame set of a given function remains a challenging open problem in time-frequency analysis. In this paper, we establish new regions of theframe set of the second-order B-spline. Our method uses the compact support of this function to partition a subset of the putative frame set and finds an explicit dual window function in each subregion. Numerical evidence indicates the existence of further regions belonging to the frame set.
Keywords: Gabor frames; Frame set and B-splines